2020
DOI: 10.1186/s12985-020-01401-2
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro virucidal activity of Echinaforce®, an Echinacea purpurea preparation, against coronaviruses, including common cold coronavirus 229E and SARS-CoV-2

Abstract: Background Coronaviruses (CoVs) were long thought to only cause mild respiratory and gastrointestinal symptoms in humans but outbreaks of Middle East Respiratory Syndrome (MERS)-CoV, Severe Acute Respiratory Syndrome (SARS)-CoV-1, and the recently identified SARS-CoV-2 have cemented their zoonotic potential and their capacity to cause serious morbidity and mortality, with case fatality rates ranging from 4 to 35%. Currently, no specific prophylaxis or treatment is available for CoV infections. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 41 publications
2
62
0
2
Order By: Relevance
“…The immunomodulatory activity of Echinacea induces an antiviral response by influencing PRR, PAMP, and DAMPs. Echinacea have been shown to be effective against rhinoviruses [ 121 ], influenza virus [ 122 ], RSV [ 44 ], herpes virus [ 44 ], adenoviruses [ 44 ], and coronaviruses [ 43 , 123 ]. Another compound, chicoric acid, has also shown potent antiviral effects against herpes simplex, influenza, enterovirus, hepatitis B virus, HIV, vaccinia virus, and vesicular stomatitis virus (VSV)-Ebola [ 124 ].…”
Section: Antiviral Potential Of Echinaceamentioning
confidence: 99%
See 3 more Smart Citations
“…The immunomodulatory activity of Echinacea induces an antiviral response by influencing PRR, PAMP, and DAMPs. Echinacea have been shown to be effective against rhinoviruses [ 121 ], influenza virus [ 122 ], RSV [ 44 ], herpes virus [ 44 ], adenoviruses [ 44 ], and coronaviruses [ 43 , 123 ]. Another compound, chicoric acid, has also shown potent antiviral effects against herpes simplex, influenza, enterovirus, hepatitis B virus, HIV, vaccinia virus, and vesicular stomatitis virus (VSV)-Ebola [ 124 ].…”
Section: Antiviral Potential Of Echinaceamentioning
confidence: 99%
“…It is well-studied, extensively used, widely accessible reputed herbal immunomodulator and antiviral which is gaining importance due to its therapeutic benefits along with preclinical and clinical studies. Among numerous herbal drugs, Echinacea has been proposed as a potential herbal drug candidate for novel coronaviruses [ 38 , 39 , 40 , 41 , 42 ] and a recent experimental ( in vitro ) study, showed that Echinacea has inhibitory activity against SARS-CoV-2 [ 43 ]. It is also considered as a functional food ingredient [ 60 ].…”
Section: Limitations On the Use Of Echinaceamentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous pharmaceuticals and biotechs have joined the race to find vaccines, prophylactic and therapeutic candidates against COVID-19 [ 39 ] and this includes a focus on new candidates. Apart from the candidates identified in this review, other molecules cited in the published literature and in the media as possible prophylactic candidates include existing herbal extracts such as Echinacea [ 40 , 41 ], nicotine [ 42 ], and new molecules including PAC-MAN (prophylactic antiviral CRISPR in human) for viral inhibition [ 43 ] and DARPIN®, multi-target binding neutralizing proteins [ 44 ]. The underrepresentation of new molecules in ongoing RCTs is likely in part due to the relative novelty of this virus, and the necessary time lag to develop new molecules prior to testing them in clinical trials.…”
Section: Discussionmentioning
confidence: 99%